Printed circuit board recycling: a focus on a novel, efficient and sustainable process for spent critical metals recovery - Charpentier, Nicolas M.; Xia, Dong; Gabriel, Jean-Christophe P. (Comptes Rendus. Chimie)
In this article, we present a novel and sustainable approach for recycling printed circuit boards (PCBs), potentially enabling the complete transformation of collected waste into reusable raw materials. Our methodology starts with the disassembly of PCBs for the extraction of all electronic components (ECs). These ECs are then subjected to a classification process using advanced sorting techniques, including machine vision and multi-energy X-ray transmission spectroscopy powered by artificial intelligence, which allows ECs with similar elemental composition to be accurately sorted together. This sorting approach can effectively enrich the target elements up to 10,000 times their original content, enabling their subsequent recovery through dedicated physico-hydrometallurgical processes. These tailored methods offer enhanced efficiency and improved environmental sustainability for recycling valuable and critical elements such as rare earth elements, tantalum, and platinum group metals. Notably, our approach not only demonstrates superior sustainability but also offers increased economic viability, making it a more financially profitable solution.